Colorectal Cancer Screening Program in Songjiang district, Shanghai between 2015 and 2017: Evaluation of participation rate and the associated factor. Issue 32 (12th August 2022) - Wu, Yiling; Saito, Hiroaki; Ozaki, Akihiko; Tanimoto, Tetsuya; Jiang, Yonggen; Yang, Peng; Li, Jing; Zhou, Zhiming; Zhu, Xiuguo; Lu, Fei; Kanemoto, Yoshiaki; Kurokawa, Tomohiro; et al.
Abstract : Little is known about the participation rate of newly implemented colorectal cancer (CRC) screening programs in China. Our goals were to identify factors associated with nonparticipation for CRC screening in Songjiang District, Shanghai. We analyzed individuals included in an observational cohort study from 4 towns (Xin Qiao, She Shan, Mao Gang, and Zhong Shan) in Songjiang District. The participation rate was calculated for the CRC screening program based on a fecal immunochemical test and a risk assessment questionnaire between 2015 and 2017 inclusive. Of the 27, 130 individuals eligible for inclusion in this study, 20, 863 (76.9%) participated in CRC screening at least once during 2015 and 2017. The factors linked with nonparticipation were; being male (odds ratio [OR] 0.87, 95% confidence interval [CI] 0.82–0.93, P < .01), unmarried (OR 0.71, 95% CI 0.64–0.80, P < .01), having a high education level (middle school, OR 0.82, 95% CI 0.74–0.90, P < .01, high school or above, OR 0.64, 95% CI 0.57–0.73, P < .01), absence of chronic disease (OR 0.90, 95% CI 0.85–0.96, P < .01), and living in 2 out of the 4 towns covered (Xin Qiao, OR 0.72, 95% CI 0.66–0.78, P < .01, Zhong Shan, OR 0.29, 95% CI 0.26–0.31, P < .01). The current study revealed several associated factors with nonparticipation for the CRC screening in Songjiang district. These findings will help identify target populations that require an individualized approach to increase the participation rate.